(untitled) (Journal of Atomic and Molecular Sciences, 2011)
We have studied the structural, electronic and magnetic properties of (ZnTe)_12 clusters doped with one (monodoped) and two (bidoped) Cr atoms in terms of a first-principles method. Substitutional, exohedral, and endohedral doping are considered. The exohedral isomer is found to be most favorable in energy for monodoped clusters, while the endohedral isomer is found to be most favorable for bidoped ones. The magnetic coupling between the Cr atoms is mainly governed by the competition between direct Cr-Cr antiferromagnetic (AFM) interaction and the ferromagnetic (FM) interaction between two Cr atoms via Te atom due to strong p-d hybridization. Calculations indicate that the substitutional bidoped (ZnTe)_12 clusters favor the FM state, which has potential applications in nanoscale quantum devices.